A monetary-valuation analysis of the footpath/road tradeoff of Western Australian local government authorities - Brown, Alistair (A R R B Group Ltd, 2014)
This study uses a monetary-valuation analysis of the footpath/road trade-off ratio of local government authorities to gather a sense of the recognition and valuation of footpaths for transport policy. The analysis shows that the average valuation local government authorities place on local footpaths is approximately $1 per $77.41 placed on local roads, with most authorities preferring to use the historical cost method to value their footpaths. Further analysis, employing multiple regression, shows that population density and an authority’s current ratio are highly significant for monetary valuations placed by local government authorities for the footpath/road trade-off. In light of the results there appears room for local government authorities to step up their expenditure on footpath infrastructure.